Exploring the feasibility in using medical computerized tomography to monitor growth progression in tissue engineered construct prepared from cells seeded on Poly(Lactic-co-Glycolic Acid) based scaffolds - Mat Nawi, Nur Farhana; Zainuddin, Zainul Ibrahim; Md Nazir, Noorhidayah; Mohamad, Mohd Yusof; Ahmad Radzi, Muhammad Aa’zamuddin; Hashim, Rosyafirah; Sha'ban, Munirah (Kulliyah of Engineering, International Islamic University Malaysia, 2016)
This study attempted to examine the feasibility of using medical Computerized Tomography (CT) imaging scanner to monitor the growth of tissue engineered constructs (TECs) in vitro. A preliminary CT examination was performed on TECs prepared from serially expanded chondrocytes seeded on poly (lactic-co-glycolic acid) (PLGA) based scaffolds that acted as cell carriers. One day old PLGA with fibrin and cells (PFC), PLGA and cells (PC) as well as PLGA with Fibrin (PF) constructs were stored in normal saline prior to CT examination. The kVp used was 80 Kvpwhile the effective mAs was 11 mAs. Sharp kernel was chosen as the reconstruction parameters and slice thickness used was 0.1mm.A PLGA without cells or fibrin was used as control. X-ray attenuation of TECs, measured in Hounsfield units (HU) or, also known as CT values were observed. The results indicated that the control PLGA, the PFC, the PC and also the PF constructs gave CT values between -665HU to 477HU, between 149HU to 181HU, between -120HU to 263HU and -209HU to 185HU respectively. These initial results indicate that the x-ray absorption-based quantitative differentiation between TECs could be appreciated. The CT values documented suggest that the differences in attenuation values are dependent on the condition of the scaffolds or the TECs themselves. Furthermore, the use of intravascular ultrasound (IVUS) software installed in the CT system was found to be useful in appreciating the different compositions within the scanned samples. It is hoped that the outcomes of this preliminary study can serve as a baseline for future research to look for an alternative method to quantitatively monitor the growth of TECs in vitro as well as in vivo.